STRATEGIES FOR DEVELOPING LISTENING SKILLS IN FOREIGN LANGUAGE LEARNERS - Mansurov O‘lmas Fazliddinovich (Modern American Journals, 2025)
Listening comprehension is a fundamental component of language acquisition, particularly in the context of learning a second language. This paper explores effective strategies for enhancing listening skills among foreign language learners. Drawing upon existing literature and empirical studies, the research identifies key approaches such as pre-listening activities, interactive listening tasks, and the integration of technology. The findings suggest that a combination of these strategies can significantly improve learners' listening proficiency.
Keywords: Listening comprehension, foreign language learning, pre-listening activities, interactive tasks, technology integration